1973
DOI: 10.1002/pssa.2210200222
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced defects in n-type and p-type silicon

Abstract: n‐type and p‐type silicon crystals were quenched from 900 to 1400 °C into a cooling liquid. From Hall coefficient and conductivity measurements a model was deduced, in which the changed electrical properties of the quenched samples are caused by an additional shallow donor and a more complex type of defect which acts – depending on Fermi level – as an acceptor or donor, respectively. An energy level nearer than 0.07 eV to the bottom of the conduction band was estimated for the shallow donor whereas an acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…Seeger and Chik [ l ] concluded that qnenching phenomena in Xi are more complex than in Ge and that the experimental information a t present is not, sufficient to attempt an identification of the site occupied by the donor. This view is substantiated by more recent work [43], [42].…”
Section: Quenching and Annealing Expeviments In Sisupporting
confidence: 67%
See 3 more Smart Citations
“…Seeger and Chik [ l ] concluded that qnenching phenomena in Xi are more complex than in Ge and that the experimental information a t present is not, sufficient to attempt an identification of the site occupied by the donor. This view is substantiated by more recent work [43], [42].…”
Section: Quenching and Annealing Expeviments In Sisupporting
confidence: 67%
“…4) has been used. This diffusivity range embraces the reported Au interstitial diffusivity of 2 3 x Quenching experiments in Si by different workers show general agreement on the existence of a donor defect [43]. Seeger and Chik [ l ] concluded that qnenching phenomena in Xi are more complex than in Ge and that the experimental information a t present is not, sufficient to attempt an identification of the site occupied by the donor.…”
Section: Quenching and Annealing Expeviments In Sisupporting
confidence: 66%
See 2 more Smart Citations
“…I n this way, the existence of different TID types can be proved, one of them also without the participation of iron. As regards the distinction of TID's, this paper exceeds presented results [3,4] and, thus, gives an explanation to some of the existing contradictions.…”
Section: Introductionsupporting
confidence: 40%